STRATEGI PEMASARAN MEDIA SOSIAL: MEMBANGUN CITRA MEREK DAN KEPERCAYAAN UNTUK MENINGKATKAN MINAT BELI PRODUK RAMAH LINGKUNGAN - Imammudin, Yusuf; Putri, Tyas Eka Permata; Rohmawati, Shintya Putri (Jurnal Edukasi Ekonomi, 2024)
Growing consumer knowledge of environmental issues has fueled demand for ecologically friendly items, particularly cosmetics, impacting consumer loyalty and product diversification. Social media marketing is critical in building a positive brand image and influencing purchasing decisions for environmentally friendly products. The purpose of this study is to look into the impact of social media marketing on brand image, brand trust, and consumer purchase interest in environmentally friendly products, namely Avoskin Skincare products. The study employs quantitative approaches and involves active social media consumers who are familiar with Avoskin and live in Surakarta. Data were collected via an online questionnaire with a 1-5 Likert Scale and a sample size of 170 respondents. Data analysis utilizing the SEM-PLS approach reveals a positive correlation between social media marketing, brand image, brand trust, and consumer purchasing interest. These findings demonstrate that an effective social media marketing strategy can form positive opinions and improve brand confidence, ultimately encouraging consumers to purchase environmentally friendly products like Avoskin